Penerapan Algoritma Hybrid Affine Cipher dan RSA Terhadap Sistem Keamanan - Togar Timoteus Gultom (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
The higher the value of a data, the higher the risk of damage or loss of the data. This is understandable, because high-value data is like "life" for humans, so if a data has been damaged or even lost, then the data has no meaning anymore. There are many ways to protect data. Data protection uses a method called encryption process which encodes the code in the original text into arbitrary characters. So that the contents of the encrypted data can be read again, it is necessary to change the contents of the data to its original form, this process is called decryption. In this study, a File Security System Protection Application Design was made using a hybrid affine cipher and the RSA algorithm. This application is made using the Delphi 7.0 Programming Language.